Teaching Interpersonal Psychotherapy (IPT) in an MSW Clinical Course. Issue 3 (27th May 2019) - Corcoran, Jacqueline; Stuart, Scott; Schultz, Jessica
ABSTRACT: Interpersonal Psychotherapy (IPT) is a relatively brief psychodynamic intervention of approximately 12 sessions focusing on how current interpersonal relationships have contributed to a person's mental health symptoms. Areas targeted for work involve significant role transitions, grief and loss, and interpersonal disputes. IPT is an evidence-based treatment for depression, bulimia nervosa, and binge eating disorders. Despite these advantages, social work students rarely receive instruction on the delivery of IPT in their graduate programs. The purpose of this project, therefore, was to begin to address this gap by implementing an IPT component in a clinical practice course and testing student knowledge pre- and post-test. An example of sample assignments involving application of IPT to student fieldwork is provided. The sample in this study involved a small number of students enrolled in a clinical course taught in the first semester of the second year of training. Students improved their knowledge score at a statistically significant level. Implications of the study are explored, with the main conclusion being that more clinical majors in MSW programs be exposed to IPT.